Keragu-raguan terhadap Agama: Wacana Humanisme dan Eksistensialisme - Mawardi Mawardi (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Religion has a significant role on people‟s lives. So the community is very important to attend and maintain their religious life. Society does not need to create a “new religion” to address issues of human life. When people lose grip norms that make life not worth , religion will serve as a protective ceiling in various approaches and views. Each of these disciplines to define and view religion in their own way according to his interests. This can be seen for instance from view of religion given by the flow of humanism and existentialism.